A checklist of fishes of eastern Terai of Nepal - Kumar, Prakash; Barma, Shishir Kumar; Subba, Bharat Raj (Nepalese Journal of Biosciences, 2013)
An attempt has been made to survey the existing fish species of the eastern Terai of Nepal. In three months duration, fifty three fish species belonging to twenty families were recorded. The anthropogenic activities were mostly found responsible for decline of fish species in this region. DOI: http://dx.doi.org/10.3126/njbs.v1i0.7473 Nepalese Journal of Biosciences 1: 63-65 (2011)